INOVASI PEMBELAJARAN AKUNTANSI DI YOUTUBE MENYONGSONG INDONESIA EMAS 2045 - Agus Suharsono (Ultimaccounting Jurnal Ilmu Akuntansi, 2021)
Abstract — Indonesia is currently launching an era of demographic bonuses in which the productive population is more dominant than the non-productive population. They are the golden generation that will realize Indonesia Golden 2045. The subject of this research is about innovation in accounting learning to realize the educational goals of 2020, namely capacity building, modernization of the learning process with the use of technology, strengthening services, easy access, and can be felt by all levels of society. The method used is qualitative, data in the form of accounting learning videos on YouTube which are analyzed logically-inductively and then presented descriptively. The results of the study note that there is already an accounting learning video on YouTube but its nature is scattered so that it cannot be used as a complete learning medium for this purpose it is necessary to collaborate with several parties to create an integrated Accounting Learning account and complete one course in accordance with the established curriculum. In order for the video display to suit the tastes of the learner, the making involves students across campus. A complete accounting learning video can be used as a learning media with a blended learning system so that face-to-face meeting is more effective for practice and case studies. Keywords: Accounting Learning; Millennial Generation; YouTube; Indonesia Gold 2045.